Severe heat shock induces nucleolar accumulation of mRNAs in Trypanosoma cruzi - Nazer, Ezequiel (2012)
Several lines of evidence have shown that, besides its traditional function in ribosome biogenesis, the nucleolus is also involved in regulating other cellular processes such as mRNA metabolism, and that it also plays an important role as a sensor and coordinator of the stress response. We have recently shown that a subset of RNA Binding Proteins and the poly(A)+ RNA are accumulated into the Trypanosoma cruzi nucleolus after inducing transcription inhibition with Actinomycin D. In this study, we investigated the behaviour of the T. cruzi mRNA population in parasites subjected to severe heat shock, an environmental stress that also decreases the rate of RNA synthesis. We found that the bulk of poly(A)+ RNA is reversibly accumulated into the nucleolus when exposing T. cruzi epimastigote forms to severe heat shock. However, the Hsp70 mRNA was able to bypass such nucleolar accumulation. Together, these data reinforce the idea about the involvement of the T. cruzi nucleolus in mRNA metabolism during an environmental stress response. Interestingly, T. brucei procyclic forms did not induce nucleolar accumulation of poly(A)+ RNA under such stress condition, suggesting that different trypanosomatids have adopted different responses to deal with the same stress conditions.